2011
DOI: 10.1111/j.1574-6968.2011.02419.x
|View full text |Cite
|
Sign up to set email alerts
|

An endo-β-N-acetylglucosaminidase from Enterococcus faecalisV583 responsible for the hydrolysis of high-mannose and hybrid-type N-linked glycans

Abstract: It has been demonstrated previously that Enterococcus faecalis produces secreted endoglycosidases that enable the bacteria to remove N-linked glycans from glycoproteins. One enzyme potentially responsible for this activity is EF0114, comprising a typical GH18 endoglycosidase domain and a GH20 domain. We have analyzed the other candidate, EF2863, and show that this predicted single domain GH18 protein is an endo-β-N-acetylglucosaminidase. EF2863 hydrolyzes the glycosidic bond between two N-acetylglucosamines (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The endoglycosidases resemble chitinases in amino acid sequences but no, or only little, chitinolytic activity has been demonstrated for these enzymes. Examples of such endoglycosidases include enzymes produced by Enterococcus faecalis (Collin & Fischetti, 2004;Bøhle et al, 2011) and Streptococcus pyogenes (Collin & Olsén, 2001). We will not describe the role of these enzymes as virulence factors in any detail, since this has been the topic of another recent review (Garbe & Collin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The endoglycosidases resemble chitinases in amino acid sequences but no, or only little, chitinolytic activity has been demonstrated for these enzymes. Examples of such endoglycosidases include enzymes produced by Enterococcus faecalis (Collin & Fischetti, 2004;Bøhle et al, 2011) and Streptococcus pyogenes (Collin & Olsén, 2001). We will not describe the role of these enzymes as virulence factors in any detail, since this has been the topic of another recent review (Garbe & Collin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…CBP21 catalysis was shown to be dependent on molecular oxygen, an external electron donor, and the presence of a metal ion cofactor (6), later identified as copper (19). Copper ions have been identified to activate AA10 (19,23), AA9 (7,9,10), and AA11 LPMOs (12). In addition to CBP21, LPMO activity has only been demonstrated for two other CBM33s so far, a celluloseactive CBM33 from Streptomyces coelicolor (CelS2 (8)) and a chitin-active CBM33 from Enterococcus faecalis (EfaCBM33A (24)), the latter of which is the subject of this study.…”
mentioning
confidence: 99%
“…Only mammal (but not insect) guts were found to contain some of these proteins, although to lesser extents compared to the lynx gut and never possessing this entire set, with the Canis familiaris gut containing the highest number of these genes (0.031% of all ORF; Table S3). Acid GLA α-galactosidases (15 hits) hydrolyze the terminal α-galactosyl moieties from complex glycolipids and glycoproteins such as ceramide trihexoside [61]; sialidases (8 hits) help break down large sugar molecules (oligosaccharides) attached to certain glyco-proteins by removing sialic acid [62]; HYA hyalurono-glucosaminidases (7 hits) catalyze the hydrolysis of hyaluronic acid and similar glycosaminoglycans that are found in numerous animal tissues, such as joints, cartilage, skin and eyes [63]; NAGLU (8 hits), GALNS (7 hits), GNS (5 hits), ARSA (7 hits) and IDS (2 hits) may contribute to the putative hydrolysis of the N -acetylgalactosamine (GalNAc) and N -acetylglucosamine (GlcNAc) components of animal tissues [64][66]. Binning analysis suggested that all but one of this second set of sequences binned to several genomes derived from bacteria belonging to the Bacteroidetes phylum, most likely of the Bacteroides genus (Table S4).…”
Section: Resultsmentioning
confidence: 99%